Composition and biological activity of Artemisia messerschmidiana essential oil - Suleimen, Ye; Mamytbekova, G.; Serikbai, G.; Birimzhanova, D.; Doudkin, R.; Gorovoy, P.; Ross, S.; Martins, C.H.G. (Fundamental and Experimental Biology, 2025)
The study of the chemical composition of essential oils and the evaluation of their biological activity is an important task in the search for new sources of medicinal plants. This article presents the results of the evaluation of the composition and biological activity of essential oil isolated from Artemisia messerschmidtiana from the Far East. The essential oil was extracted by hydrodistillation. The obtained essential oil was tested for antimicrobial, antifungal, antimalarial, cytotoxic, antitubercular, and antileishmanial activity. Analysis of the essential oil composition by gas chromatography-mass spectrometry revealed the presence of 43 components. The maximum content was noted for 1,8-cineole, camphor, and α-campholenal. Testing of the essential oil revealed weak antimicrobial, fungicidal, and antimalarial activity and high cytotoxic activity. No antituberculosis or antileishmaniasis activity was detected in the essential oil. The results contribute to the knowledge of the biological activity of components of the genus Artemisia L.